CARICA STRUDEL: CULINARY INNOVATION TO STIMULATE SENSORY AND FUN MATHEMATICS ABILITIES IN CHILDREN - Hanifah, Desty Putri; Bayu, Iqbal; Majid, Ahmad Tarikul (CATHA SAINTIFICA, 2024)
The study aims to examine the educational impact of introducing Carica Strudel on sensory and mathematical abilities in children aged 4-7 years in Wonosobo. Carica Strudel represents a culinary innovation that combines carica with strudel. It is not only a local culinary dish but also has the potential to serve as an effective learning tool. The research method employed is a descriptive quantitative approach. The research sample consisted of 20 children participating in the "Kitchen Exploration: Carica Strudel" activity was organized by Teman Penjelajah Community in collaboration with Patara. Data were collected through participant observation, in-depth interviews, and document analysis. The research procedures included the preparation, implementation, and data analysis stages. The research procedures consist of three stages: preparation, implementation, and data analysis. The validity of the data is guaranteed through triangulation of sources and methods, as well as member checking. The findings of the research indicate that the introduction of Carica strudel can stimulate children's various sensory abilities, including taste, visual perception, texture, and aroma. In addition, this activity facilitates the development of mathematical skills, including measurement, basic calculations, geometry, pattern recognition, estimation, simple data analysis, and an understanding of temperature and time. Carica Strudel is not only a culinary innovation that reflects local wisdom; it can also be utilized as an engaging and meaningful learning tool for children. This research offers new insights into the integration of local culinary delights in children's education, particularly in the development of sensory and mathematical abilities